A Political Economy of Wellbeing/Wellness in Nigeria - Adodo, Anselm (Mediterranean Journal of Social Sciences, 2022)
Since the turn of the new millennium, which was the period of clear comparison and computation of the misery index, Nigeria had always record low in the index for the report. Within the last three years, the misery index that was published has shown that Nigeria is the sixth (6th) most miserable country that one can reside. This measure of misery index was also substantiated by the recent report from the World Bank on the issue of poverty, inequality, and wellness. However, it seems to be an intensified interest in how Nigeria will overcome such an unpleasant pattern. In this research, the study examined how macroeconomic indices in enhancing people’s wellbeing—utilising economic growth, monetary policy position, and governance efficiency as, unemployment, interest rate, and inflation rate for macroeconomic performance indicators. The conclusions drawn suggest that economic growth, resulting in the advancement of wellbeing via allocative as well as distributive productivity is possible. Second, there is a stiffening effect on the wellbeing of contractionary monetary policy which increases interest rates and unemployment rates. The outcome extracted also shows that unnecessary domestic lending characteristics of the Nigerian economic system invalidate the wellbeing of the Nigerian people. Therefore, it proposed that the monetary authority reevaluate its present position on sustaining a high level of rediscount rate. Received: 17 November 2021 / Accepted: 30 December 2021 / Published: 5 January 2022